The importance of health articles in the electronic newspaper xandan - Roza Hamawais Hamamirza (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The importance of health articles on electronic Khandan newspaper. Scientific research is one of the main principles of development in this century, researching in press field is important these days because press and media are part of every one’s daily life. every one is strictly has involved with in using one of connection devices at least so as to reach his demands. Apparently the electronic newspapers as a crucial part of mass media it pays to focus on issue, because every days the readers of online newspapers are increasing. It is clear that success of any kind of media and press has a great relation to the contents and type of its news and articles, so the this research ( the importance of health articles on electronic newspaper) is so important. It is obvious that nowadays we pay attention to obtain information about some common sorts of psychology, mental and body illness and disease. It has positive and negative side on human being. Nowadays those healthcare textures are being published and released on Internet websites are various , so this research is divided into three main sections: The first section is devoted to the style of research. The second section is about theory . The third section is about the practice. The conclusions that the researcher has got are: the priority of Khandan electronic newspaper is about general health care in comparison to other aspects. The sources of Khandan online newspaper is other mass medias and the title of news are being noticed to get the readers’ attention. The neutrality of the newspaper ,the researcher has reached this fact that only one side of news have been published. The publication style of health articles on newspapers, the researcher has reached this conclusion that the newspaper works on expressing the cause and effect.